BDNF-Val66Met-polymorphism impact on cortical plasticity in schizophrenia patients: a proof-of-concept study - Strube, Wolfgang; Rietschel, Marcella (The international journal of neuropsychopharmacology, 2015)
Background:Brain-derived neurotrophic factor (BDNF) has been shown to be a moderator of neuroplasticity. A frequent BDNF-polymorphism (Val66Met) is associated with impairments of cortical plasticity. In patients with schizophrenia, reduced neuroplastic responses following non-invasive brain stimulation have been reported consistently. Various studies have indicated a relationship between the BDNF-Val66Met-polymorphism and motor-cortical plasticity in healthy individuals, but schizophrenia patients have yet to be investigated. The aim of this proof-of-concept study was, therefore, to test the impact of the BDNF-Val66Met-polymorphism on inhibitory and facilitatory cortical plasticity in schizophrenia patients.Methods:Cortical plasticity was investigated in 22 schizophrenia patients and 35 healthy controls using anodal and cathodal transcranial direct-current stimulation (tDCS) applied to the left primary motor cortex. Animal and human research indicates that excitability shifts following anodal and cathodal tDCS are related to molecular long-term potentiation and long-term depression. To test motor-cortical excitability before and after tDCS, well-established single- and paired-pulse transcranial magnetic stimulation protocols were applied.Results:Our analysis revealed increased glutamate-mediated intracortical facilitation in met-heterozygotes compared to val-homozygotes at baseline. Following cathodal tDCS, schizophrenia met-heterozygotes had reduced gamma-amino-butyric-acid-mediated short-interval intracortical inhibition, whereas healthy met-heterozygotes displayed the opposite effect. The BDNF-Val66Met-polymorphism did not influence single-pulse motor-evoked potential amplitudes after tDCS.Conclusions:These preliminary findings support the notion of an association of the BDNF-Val66Met-polymorphism with observable alterations in plasticity following cathodal tDCS in schizophrenia patients. This indicates a complex interaction between inhibitory intracortical interneuron-networks, cortical plasticity, and the BDNF-Val66Met-polymorphism. Further replication and validation need to be dedicated to this question to confirm this relationship.